Chinese residents' knowledge about and behavior towards dairy products: a cross-sectional study - Jun Wei; Jian Wang (BMC, 2023)
Abstract Background Chinese residents generally had insufficient intake of dairy products. The correct mastery of dairy related knowledge helps to develop a good habit of dairy intake. Dairy intake and purchasing behavior were related to multiple factors. As an attempt to lay a scientific basis for guiding the rational intake of dairy by Chinese residents, we launched a survey to discover Chinese residents' knowledge about dairy product, intake and purchasing behavior of dairy and its influencing factors. Methods An online survey was conducted from May to June 2021, and 2500 Chinese residents aged 16-65 were selected using the convenient sampling method. A self-designed questionnaire was adopted. Analysis of the demographic and sociological factors influencing Chinese residents' knowledge about dairy products, behavior towards dairy intake and purchasing were measured. Results The average score of knowledge about dairy product of Chinese residents was 4.13 ± 1.50 points. 99.7% of the respondents considered that drinking milk was beneficial, whereas only 12.8% gained a correct insight into the specific benefits of drinking milk. 4.6% of the respondents correctly knew what nutrients they could get from milk. 4.0% of the respondents could correctly identify the type of dairy product. 50.5% of the respondents knew that adult should drink at least 300 ml milk per day. Female, young and high-income residents had better dairy knowledge, while residents with lactose intolerance and whose family members do not have a milk-drinking habit had worse dairy knowledge (P < 0.05). On average, Chinese residents consumed 255.61 ± 88.40 ml dairy product per day. The elderly residents, residents with low education level, residents who lived with family members without milk-drinking habits and residents with poor knowledge of dairy product had worse dairy intake behavior (P < 0.05). When purchasing dairy products, young and middle-aged people (54.20% of those aged ≤ 30, 58.97% of those aged 31-44, and 57.08% of those aged 45-59) were most concerned about whether probiotics were added to dairy products. The elderly (47.25%) were most concerned about whether dairy products were low sugar / sugar free. Chinese residents (52.24%) tended to purchase small-packaged dairy products that could be consumed easily anytime and anywhere. Conclusion Chinese residents had a lack of knowledge regarding dairy products, and their dairy intake was insufficient. We should further strengthen the popularization of dairy product related knowledge, guide residents to choose dairy products correctly, and increase the intake of dairy products by Chinese residents.